Cold plasma reactive species: Generation, properties, and interaction with food biomolecules. (30th March 2023) - Dharini, M.; Jaspin, S.; Mahendran, R.
Graphical abstract: Highlights: Combining gases for plasma generation aid in obtaining reactive species specificity. All reactive species can equally contribute to the modification of biomolecules. The reactive species present in plasma decide the type of reaction that takes place. Reactive species identification is crucial in knowing the actual reaction in foods. Molecular dynamic simulation is a potential approach for plasma application. Abstract: Cold plasma- the fourth state of matter generated at room temperature is composed of several reactive species that account for chemical and physical changes in biological materials. Applications of plasma in food include but are not limited to maintaining safety, quality, and property modification. However, plasma application in the food sector lacks a detailed understanding of the cause of alteration in food. While several plasma reactive species could potentially be involved in biomolecular interactions, only a few reactive oxygen and nitrogen species (RONS) have been examined in detail. The lack of identifying reactive species with respect to the changes in process parameters leads to misconceptions about the actual chemical reaction. Therefore, this review explores the possibility of using different feed gases to alter species composition and emphasizes that all reactive species are equally involved in modifying food components, alongside the futuristic means of using molecular dynamics simulation to fill the knowledge gap.